Year-Long Metagenomic Study of River Microbiomes Across Land Use and Water Quality - Van Rossum, Thea; Peabody, Michael A.; Uyaguari-Diaz, Miguel I.; Cronin, Kirby I.; Chan, Michael; Slobodan, Jared R.; Nesbitt, Matthew J.; Suttle, Curtis A.; Hsiao, William W. L.; Tang, Patrick K. C.; Prystajecky, Natalie A.; Brinkman, Fiona S. L. (Frontiers in Microbiology, 2015)
Select bacteria, such as Escherichia coli or coliforms, have been widely used as sentinels of low water quality; however, there are concerns regarding their predictive accuracy for the protection of human and environmental health. To develop improved monitoring systems, a greater understanding of bacterial community structure, function and variability across time is required in the context of different pollution types, such as agricultural and urban contamination. Here, we present a year-long survey of free-living bacterial DNA collected from seven sites along rivers in three watersheds with varying land use in Southwestern Canada. This is the first study to examine the bacterial metagenome in flowing freshwater (lotic) environments over such a time span, providing an opportunity to describe bacterial community variability as a function of land use and environmental conditions. Characteristics of the metagenomic data, such as sequence composition and average genome size, vary with sampling site, environmental conditions, and water chemistry. For example, average genome size was correlated with hours of daylight in the agricultural watershed and, across the agriculturally and urban-affected sites, k-mer composition clustering corresponded to nutrient concentrations. In addition to indicating a community shift, this change in average genome size has implications in terms of the normalisation strategies required, and considerations surrounding such strategies in general are discussed. When comparing abundances of gene functional groups between high- and low-quality water samples collected from an agricultural area, the latter had a higher abundance of nutrient metabolism and bacteriophage groups, possibly reflecting an increase in agricultural runoff. This work presents a valuable dataset representing a year of monthly sampling across watersheds and an analysis targeted at establishing a foundational understanding of how bacterial lotic communities vary across time and land use. The results provide important context for future studies, including further analyses of watershed ecosystem health, and the identification and development of biomarkers for improved water quality monitoring systems.